Cardiac tamponade due to the rupture of the coronary artery fistula - Harada, Yuko; Mori, Atsuo; Abiko, Tomohiro; Saka, Shohei; Shinagawa, Toshihito; Yoshimoto, Tatsuji (Cardiovascular Diagnosis and Therapy, 2013)
Congenital coronary artery fistulas (CAFs) without symptoms are usually not considered as an indication for surgical treatment. We describe a rare case of cardiac tamponade secondary to spontaneous rupture of a CAF, which lead to death. An autopsy and pathological examination revealed that the CAF had histological abnormalities, which could have caused the rupture. This case report suggests that CAFs with extreme deformity should be considered for surgical treatment.